Enchancing Community Health Services to Combat Stunting and Non-Communicable Diseases in Ngiliran Village Poncol District, Magetan Regency - Sumasto, Hery; Wisnu, Nurwening Tyas; Triana Septianti; Mentari, Mulyananda Dwi; Sulikah (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2025)
This community service aims to strengthen community-based health services through the Primary Service Integration Posyandu (ILP) in an effort to overcome stunting and non-communicable diseases (NCDs) in Ngiliran Village, Panekan District, Magetan Regency. The health problems faced by this village include the high rate of stunting and the increasing prevalence of NCDs, such as diabetes mellitus, hypertension, and obesity. This activity involves active community participation through balanced nutrition counseling, health checks, and capacity building for posyandu cadres and local health workers. The results of the activity showed a decrease in the prevalence of stunting, an increase in public knowledge about stunting prevention and NCDs, and success in early detection through hemoglobin (Hb) and blood sugar (GDS) examinations. The program has also succeeded in strengthening cross-sector networks and creating greater awareness of the importance of healthy living behaviors at the village level. It is hoped that this activity can be sustainable and have a long-term positive impact on public health in Ngiliran Village.